Crew and controlled burn - Lindquist, Mark, photographer (Colorado State University. Libraries, 2000)
Controlled burn on SGS, with smoke, blackened grasses, burning yucca and crew (reverse of NRELSGSL_firestudy_by_MDL.jpg).
Keywords: burn; SGS; experimental; landscapes